(untitled) (Research, Society and Development, 2024)
The ecosystem of the human oral cavity is dynamic and diverse, evolving since the early stages of life. The mother plays a crucial role as the primary source of oral microflora for the baby, but as the child grows, its oral microbiota stabilizes. In hospital settings, patients with serious conditions and compromised immune systems face additional health risks. In intensive care units (ICUs), especially with intubation, the risk of pneumonia, such as ventilator-associated pneumonia (VAP), increases due to bacterial colonization in the throat resulting from inadequate oral hygiene. VAP is considered one of the main causes of prolonged ICU stays and increased mortality and costs. Various dental approaches have been implemented for mechanically ventilated patients, including dental hygiene procedures and the use of antiseptic oral hygiene solutions such as mouthwashes. However, there is still no definitive method recognized as the most effective for ensuring adequate oral health in the ICU. There is also no consensus on the subject, highlighting the continued need for research to determine best practices in dental care for critically ill patients. This work aimed to research the oral hygiene protocols adopted in ICUs, their effectiveness and benefits, highlighting VAP as one of the main concerns in this environment, through an integrative literature review.